PENGARUH MWD DAN WILLIAM FLEXION EXERCISE TERHADAP PENURUNAN NYERI PADA LOW BACK PAIN AKIBAT SPONDYLOSIS LUMBAL DI RSU HAJI MAKASSAR - Arpandjaman Arpandjaman; Yonathan Ramba (Politeknik Kesehatan Makassar, 2020)
Spondylosis is a type of osteoarthritis that attacks the spine caused by a degenerative process that disrupts the function and structure of the spine. This is because the lumbar area receives the greatest load when the body moves and when it supports weight. Besides that, the movement of carrying or lifting very heavy objects can also trigger lumbar spondylosis.This type of research uses a quasi-experimental one group pre_test and post_test design which aims to determine the effect of Micro Wave Diathermy (MWD) and William Flexion Exercise on reducing pain in low back pain due to lumbar spondylosis. While the sampling technique uses Total Sampling, namely by determining the inclusion and exclusion criteria set by the researcher. This research was conducted at the physiotherapy clinic of RSU Haji Makassar from 10 May to 10 July 2015, the samples were lumbar spondylosis patients with a total sample of 10 people who fit the inclusion criteria, namely aged 30-60 years, male and female, there were no contraindications of the two therapeutic applications, willing to be routinely treated 3 times within 2 months, and willing to be a respondent.The results showed that Microwave Diathermy (MWD) and William Flexion Exercise can reduce pain in Lumbar Spondylosis with an average pain reduction of 2.4700. Meanwhile, the results of the Paired t test obtained a value of ρ = 0.000 <α 0.05 which means that H1 is accepted so that it can be concluded that Microwave Diathermy (MWD) and William Flexion Exercise have a significant effect on reducing pain in low back pain due to spondylosis.It can be concluded that the administration of MWD and William Flexion exercise can produce a significant reduction in pain in patients with Lumbar Spondylosis and therefore it is suggested to physiotherapists in the practice area and in hospitals to use the MWD and William Flexion Exercise modalities as one of the main modalities in Lumbar Spondylosis conditions Keywords: MWD, William Flexion Exercise, Lumbar Spondylosis.